Development and validation of a bioanalytical RP-HPLC method for quantification of ifenprodil in rat plasma - Pavani Bonagiri, Narender Malothu, Srilakshmi Nallapaty, Chakravarthi Guntupalli (Journal of Applied Pharmaceutical Science, 2025)
This research aimed to develop a simple, reliable, efficient, and precise Reverse phase high-performance liquid chromatography technique for measuring or determining the quantity of Ifenprodil concentration in rat plasma. Dextromethorphan served as the internal standard (IS). The separation was achieved using the isocratic method with a Luna Phenyl hexyl column (dimensions: 150 mm × 4.6 mm, particle size: 3.5 μm) on a Waters 2,695 equipment with Empower software version 2.0. The analyte was extracted utilizing a liquid–liquid extraction technique, employing acetonitrile (ACN) as an additive. For the measurement of the drug in rat plasma, a mobile phase was utilized, consisting of a mixture of ammonium formate (pH 2.5) with formic acid (FA) and ACN, in a volumetric ratio of 60:40%. The separation procedure was performed utilizing a flow rate of 1 ml/minute and a detection wavelength of 220 nm. The retention time of Ifenprodil and IS were 2.362, and 5.603 minutes, respectively. The linearity of the separation is observed within the concentration range of 200–4,000 ng/ml, exhibiting a robust correlation coefficient of 0.9998. The validation and stability study was conducted by following the guidelines outlined by the US Food and Drug Administration. The findings obtained from the study imply that the proposed approach can be effectively employed for the pharmacokinetics and bioequivalence profiling of Ifenprodil in rat plasma.
Keywords: RP-HPLC, bioanalytical method, ifenprodil, USFDA, dextromethorphan